Association of mutation position in polycystic kidney disease 1 ( PKD1) gene and development of a vascular phenotype - Rossetti, Sandro; Chauveau, Dominique; Kubly, Vickie; Slezak, Jeffrey M; Saggar-Malik, Anand K; Pei, York; Ong, Albert CM; Stewart, Fiona; Watson, Michael L; Bergstralh, Erik J; Winearls, Christopher G; Torres, Vicente E; et al. (The Lancet (British edition), 2003)
Patients with autosomal dominant polycystic kidney disease (ADPKD) are at risk of developing intracranial aneurysms, and subarachnoid haemorrhage is a major cause of death and disability. Familial clustering of intracranial aneurysms suggests that genetic factors are important in the aetiology. We tested whether the germline mutation predisposes to this vascular phenotype. DNA samples from patients with ADPKD and vascular complications were screened for mutations throughout the PKD1 and PKD2 genes. Comparisons were made between the pkd1 and pkd2 populations and with a control PKD1 cohort (without the vascular phenotype). Mutations were characterised in 58 ADPKD families with vascular complications; 51 were PKD1 (88%) and seven PKD2 (12%). The median position of the PKD1 mutation was significantly further 5′ in the vascular population than in the 87 control pedigrees (aminoacid position 2163 vs 2773, p=0·0034). Subsets of the vascular population with aneurysmal rupture, early rupture, or families with more than one vascular case had median mutation locations further 5′ (aminoacid position 1811, p=0·0018; 1671, p=0·0052; and 1587, p=0·0003). Patients with PKD2, as well as those with PKD1, are at risk of intracranial aneurysm. The position of the mutation in PKD1 is predictive for development of intracranial aneurysms (5′ mutations are more commonly associated with vascular disease) and is therefore of prognostic importance. Since the PKD1 phenotype is associated with mutation position, the disease is not simply due to loss of all disease allele products.